Hierarchical FeCo2S4@CoFe layered double hydroxide on Ni foam as a bifunctional electrocatalyst for overall water splitting. Issue 5 (31st January 2020) - Huang, Yunxia; Chen, Xiaojuan; Ge, Shuaipeng; Zhang, Qiqi; Zhang, Xinran; Li, Wenping; Cui, Yimin
Abstract : Designing high-efficiency and low-cost bifunctional electrocatalysts for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is of great significance to produce hydrogen by water electrolysis. Abstract : Designing high-efficiency and low-cost bifunctional electrocatalysts for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is of great significance to produce hydrogen by water electrolysis. Herein, a hierarchical FeCo2 S4 @CoFe layered double hydroxide (LDH) core–shell structure catalyst was successfully fabricated via a hydrothermal–sulfuration–electrodeposition three-step method. The unique structure can provide more abundant catalytically active sites for the electrochemical reaction. The resulting FeCo2 S4 @CoFe LDH electrode only requires overpotentials of 115 and 247 mV to reach a current density of 10 mA cm −2 for the HER and OER in 1 M KOH electrolyte, respectively. The electrode also exhibits a low Tafel slope and excellent stability. Furthermore, the bifunctional catalyst for overall water splitting can exhibit a cell voltage of 1.6 V at 10 mA cm −2, along with outstanding durability for 24 h testing. This work provides a new strategy to design effective bifunctional catalysts for overall water splitting.